TECHNOLOGY-MEDIATED EDUCATION IN BRAZILIAN GOVERNMENT PLATFORMS: A COMPARATIVE STUDY BETWEEN THE VIRTUAL ENVIRONMENTS AVASUS AND AVAMEC - Rabelo, Humberto; Cordeiro, Antonio Manuel Rochette; Valentim, Janaina Luana Rodrigues da Silva; Coutinho, Karla Mônica Dantas; Melo, Luciana Protásio de; Leal, Messias Gomes de Araújo; Valentim, Ricardo Alexsandro de Medeiros (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2026)
This study aimed to comparatively analyze two Brazilian public Virtual Learning Environments (VLE), AVASUS, linked to the Ministry of Health, and AVAMEC, linked to the Ministry of Education, identifying their potential, limitations, and contributions to Technology-Mediated Education. The research, qualitative and descriptive in nature, was developed between May and September 2025, based on document analysis and direct observation of the platforms. Aspects such as pedagogical structure, usability, accessibility, thematic relevance, and social impact were examined, considering the institutional objectives and user profile of each environment. The results revealed that AVASUS stands out for its pedagogical effectiveness, coherence with health training policies, and better cost-benefit ratio per certified student, while AVAMEC presents greater thematic diversity, broader reach, and strong social impact on teacher training. Both demonstrate advances in the democratization of knowledge but face challenges related to full accessibility and optimization of the mobile experience. It is concluded that strengthening these platforms requires continuous innovation and articulated public policies, aiming at the consolidation of a quality, inclusive, and sustainable public digital education in Brazil.